Pemberdayaan Masyarakat Melalui Sosialisasi Tentang Teknik Cuci Piring Spons Dalam Upaya Pemutusan Penularan Bakteri Escherichia Patogen - Martono Martono; Siti Khadijah; Muhamad Amirul Rasyid; Pradita Ayu Fernanda (LPPM AN Nuur, 2026)
Background: One source of disease transmission that is often overlooked is kitchen utensils, especially dishwashing sponges. Sponges used continuously in damp, warm conditions and that frequently contact food scraps can become a breeding ground for various pathogenic microorganisms, including Escherichia coli (E. coli) bacteria. E. coli is an indicator of fecal contamination that can cause various health problems, such as diarrhea, urinary tract infections, and even food poisoning. Public ignorance about how to properly care for sponges, such as regular washing, drying, or periodic replacement, further increases the risk of spreading bacteria through eating utensils. Purpose: The aim of this program is to evaluate the increase in the knowledge capacity of housewives in understanding dishwashing techniques using sponges to prevent the transmission of the pathogenic bacteria Escherichia coli. Method: This Community Service Program involved health education outreach for housewives, with 22 housewives, one person from the village government, and one health education worker participating. The program included planning, implementation, evaluation, and reporting. Results: The community service activities received positive appreciation and participation from all housewives and village government officials in Gagakan, Kahuman, Polanharjo, Klaten. Based on the results of the Wilcoxon Analysis Test, there was a significant increase in knowledge after being given socialization on dishwashing techniques using sponges (p = 0.012). Conclusion: The socialization of the sponge dishwashing technique improved housewives' knowledge of the sponge dishwashing technique, thereby preventing the spread of pathogenic Escherichia coli bacteria. Therefore, it is necessary to optimize the role of housewives in community empowerment activities through the sponge dishwashing technique socialization program for effective dissemination.